2009
DOI: 10.1017/s0212610900000707
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality and Inequality in Numeracy: The Case of Latin America and the Caribbean, 1880–1949

Abstract: This article outlines the development of gender disparities in education for 28 Latin American and Caribbean countries for the period from 1880 to 1949, using age heaping techniques. We explore in particular the hypothesis of a Ushaped development of women's education during economic development, i.e., a decrease in gender equality at lower levels of overall education, and increasing gender equality at higher levels. For the downward sloping part, we find some evidence, although this part is relatively small. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
12
1
1
Order By: Relevance
“…Overall, we found that sex differences in age heaping across the Mosaic datasets are smaller than might be expected from readings of economic history and demographic literature (e.g., F€ oldv ari, van Leeuwen and van Leeuwen-Li 2012;Manzel and Baten 2009). Though it is true that in the majority of Mosaic populations (67 out of 115) women on average heaped their ages more strongly than men, we also obtained proofs that a reversed pattern was far from rare.…”
Section: Correlation Between Different Measures Of Age Heapingcontrasting
confidence: 55%
See 1 more Smart Citation
“…Overall, we found that sex differences in age heaping across the Mosaic datasets are smaller than might be expected from readings of economic history and demographic literature (e.g., F€ oldv ari, van Leeuwen and van Leeuwen-Li 2012;Manzel and Baten 2009). Though it is true that in the majority of Mosaic populations (67 out of 115) women on average heaped their ages more strongly than men, we also obtained proofs that a reversed pattern was far from rare.…”
Section: Correlation Between Different Measures Of Age Heapingcontrasting
confidence: 55%
“…16 Sex differences in age heaping at the regional level So far we have relied primarily on age heaping estimates for both sexes combined. However, within the general trend of an increase in the number of age heaping studies in recent years, gender-specific analyses have also become increasingly common (Manzel and Baten 2009;De Moor and Van Zanden 2010;F€ oldv ari, van Leeuwen and van Leeuwen-Li 2012). Against a general wisdom that in traditional societies women were generally well behind men in numerical skills (including their ability to report ages properly), these studies found mixed evidence.…”
Section: Correlation Between Different Measures Of Age Heapingmentioning
confidence: 99%
“…Numeracy is measured by the age heaping method which has been used in an increasing number of recent publications (A'Hearn, Crayen, and Baten 2009;Manzel and Baten 2009;Crayen and Baten 2010;Hippe 2012b;Hippe and Baten 2012;Baten and Hippe 2017;Diebolt, Hippe, and Jaoul-Grammare 2017).…”
Section: Methodology and Datamentioning
confidence: 99%
“… A'Hearn, Baten, and Crayen, ‘Quantifying quantitative literacy’; Baten, Crayen, and Manzel, ‘Zahlendisziplin’; De Moor and van Zanden, ‘ “Leeftijdstapelen” ’; Clark, Farewell to alms , pp. 175–81; Crayen and Baten,‘Global trends in numeracy’; Manzel and Baten, ‘Gender equality’; Cinnirella, ‘Nutritional status’; Mironov, ‘Novaya istoricheskaya demografia’; Ó Gráda, ‘Dublin Jewish demography’. …”
mentioning
confidence: 99%